KANDUNGAN TIMAH HITAM ( PLUMBUM) PADA TANAMAN PENEDUH JALAN DI KOTA DENPASAR - A.A Raka Juni Antari; I Ketut Sundra (Bumi Lestari Journal of Environment)
This study was aimed to observe the content of led substances (Pb) in Angsana,s(Pterocarpus indicus Willd) and Glodogan,s (Polyalthia longifolia Bent & Hook. F )leaves growing along the busy roads in Denpasar. The study was conducted fromNovember to December 2002. Sample were obtained from five location with busy trafficswhile another one was from un busy traffics as control. Sample were analysed at AnalyticLaboratory, Udayana University using wet digestion method, then were analysed usingAtomic Absorbance Spectrofotometer (AAS).Result showed that the lead (Pb) content in Angsana’s leave out weighed theGlodogan’s leave and Pb content on November exceeded that on December 2002. Overall,analysis of all samples, on November and December 2002, indicated that the Pb contentwas bellow the standard allowed which was 1000 ppm (?g/g)